A dialogue game for analysing group model building: framing collaborative modelling and its facilitation. (1st January 2012) - Hoppenbrouwers, Stijn; Rouwette, Etiënne
This paper concerns a specific approach to analysing and structuring operational situations in collaborative modelling. Collaborative modelling is viewed here as 'the goal-driven creation and shaping of models that are based on the principles of rational description and reasoning'. Our long term goal is to use this analysis as a basis for improvement of collaborative modelling and the development of dedicated interactive support environments. We focus on a specific, established flavour of collaborative modelling called group model building (GMB), rooted in system dynamics. GMB is the collaborative modelling of causal relations and feedback loops, and aims for the understanding of the complex influences among system variables in some system. We discuss our theoretical approach to the systematic analysis and framing of collaborative modelling as dialogue games. We then present an evaluated prototype of a dialogue game for analysing GMB: an operational framing of constrained and guided GMB conversations.